การวิเคราะห์องค์ประกอบและการศึกษาภูมิหลัง ที่สัมพันธ์กับสมรรถภาพของครูนาฏศิลป์ระดับประถมศึกษา - ภาวิณี บุญเสริม (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of this research were to study competencies of dramatic teachers at elementary education level and to study characteristics and backgrounds of the teachers who had different competencies. The samples consisted of 388 dramatic teachers at elementary education level in Bangkok under the Jurisdiction of the Metropolitan Administration and the Jurisdiction of the Office of Private Education Commission. The data of this research were collected by questionnaire and analyzed by confirmatory factor analysis and second order confirmatory factor analysis through LISREL and discriminant analysis through SPSS. The following conclusion were drawn based on the finding of this research: 1. The competencies of dramatic teachers at elementary education level consisted of 2 factors; 1) General Characteristic Factor, which could divided into 5 subfactors; academic, teaching, instructor, moral and personality 2) Specific Characteristic Factor, which could divided into 2 subfactors; knowledge of drama and skill of drama. 2. The structural model of competencies of dramatic teachers at elementary education level was consistent with empirical data. The results of the model validation indicated the chi-square, goodness of fit test was 1.15; p = 0.56, df = 2, GFI = 1, AGF = 0.99, and RMR = 0.00. 3. The background variable discriminating competencies of dramatic teachers divided into 2 factor. First, the general characteristic variable consisted of age 30-49,experience and training. Second, the specific characteristic consisted of dramatic major , small size of school and teaching period. The such variable could discriminate groups of dramatic teachers with the 42.3 percen of correctness.